EDUCATION FOR THE PUBLIC ACCOUNTING ON THE COLLEGIATE LEVEL. - Scovill, H. T. (The Accounting Review, 1946)
Abstract This article focuses on education for public accounting on the collegiate level. There is little opportunity ordinarily for comparing an accountant to an apple dumpling or to a can of tomatoes, but it can be said without hesitation that in either case the quality of the raw material can have a great effect on the finished product. In the case of the accountant, however, there are some qualities which are very difficult to detect or evaluate by casual observation, and which are nearly impossible to create if they are not present in the undeveloped material. Either an institution or an individual in outlining plans for offering or receiving an education for public accounting should think of the objectives of the educational processes. The objectives can be assembled after one has given much thought to the types of duties and contacts of the accountant in his professional world from day to day. In literature, sciences, and some of the social sciences, however, the accountant will find it necessary to renew his acquaintance with some phases thereof from time to time in order to feel at home in a discussion that might arise in some of his numerous contacts.